Validation of the polyvoids in the design of bituminous mixtures with coal tar as a binder - Ochoa, R.; Grimaldo, G. (Revista Ingeniería de Construcción, 2018)
The world has developed different methodologies for the design of asphalt mixtures; each of which is intended to optimise and find the optimal combination of materials that allow them to be resistant under specific travel, climate and structural support conditions. This article presents the results of an investigation which utilised coal tar as a binding agent for road surface mixtures and carried out a comparison of results of the physical and mechanical properties of sample bituminous mixtures produced by two distinct methodologies, Marshall and Ramcodes. Finally, an analysis was carried out on the suitability of tar as a binding agent and on utilising the Ramcodes methodology when designing mixtures.